HUBUNGAN ANTARA TINGKAT STRES DENGAN KUALITAS TIDUR PADA WARGA BINAAN DI LEMBAGA PEMASYARAKATAN KLAS IIA YOGYAKARTA - Dheska Arthyka Palifiana; Ratih Kumoro Jati (Universitas Jenderal Achmad Yani Yogyakarta, 2018)
Background: To have rest or to sleep is basic need that needed by everyone. To have enough rest or sleep will make body functioned optimally. By sleeping people can restore or to rest the physical after whole day activities, it can reduce stress and anxiety. It also improve concentration and improve ability when doing daily activities. Factors that affect quality and quantity of sleep include ill, fatigue, environment, lifestyle, emotional stress, diet, smoking, stimulant, alcohol, and motivation. The stress level on assisted citizen of woman’s prisoner will be more severe than who are not in prison so as stress can be overcome then the quality of sleep becomes better. Objective:To know the correlation between stress levels and sleep quality on assisted people in woman Penitentiary class II A Yogyakarta. Methods: The research was conducted at women's prison class II A Yogyakarta. Research population was 117 women prisoners. The sample was 50 women prisoners. Type of the research was descriptive analytic research with cross sectional design. Statistical analysis used chi square. The sampling technique used purposive sampling. Results: The stress level was mostly in high category as many as 17 respondents experienced stress (34%). Sleep quality of the respondents were mostly in bad category as many as 38 respondents (76%). There is a correlation between stress level and sleep quality on women prisoners in Penitentiary class II A Yogyakarta with p-value (0.033). Conclusion: There is a correlation between stress level and sleep quality on women prisoners in Penitentiary class II A Yogyakarta. Keywords: Stress level, sleep quality, assisted people, penitentiary